MIGRACIYA TARIYXÍ – BUL INSANIYAT TARIYXÍ - Utepova, Genjexan Baltabaevna (SCIENCE and SOCIETY, 2026)
This article mainly discusses the migration movements (migration) of the world’s population in historical periods, economic, demographic, political, social, and ecological factors influencing migration movements.